2011
DOI: 10.1074/jbc.m110.171645
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Water-soluble, Ligand-binding Concatameric Extracellular Domains of the Human Neuronal Nicotinic Receptor α4 and β2 Subunits in the Yeast Pichia pastoris

Abstract: Nicotinic acetylcholine receptors (nAChRs) are ligand-gated cation channels that are responsible for cell communication via the neurotransmitter acetylcholine. The predominant nAChR subtype in the mammalian brain with a high affinity for nicotine is composed of ␣4 and ␤2 subunits. This nAChR subtype is responsible for addiction to nicotine and is thought to be implicated in Alzheimer and Parkinson diseases and therefore presents an important target for drug design. In an effort to obtain water-soluble, ligand-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
1
2
0
2
Order By: Relevance
“…Notably, the presence of a major band at (30 kDa) is well correlated with the size of the monomeric α-7 nAChR ECD. It should be noted that these results were in agreement with the expression of human neuronal nicotinic receptor α4 and β2 subunits in P. pastoris, which were also expressed in glycosylated forms [20]. Besides P. pastoris, the glycosylation of recombinant α-7 nAChR was also detected in the proteins expressed in Xenopus oocytes [21].…”
Section: Purification Of Recombinant Human α-7 Nachr Ecdsupporting
confidence: 84%
“…Notably, the presence of a major band at (30 kDa) is well correlated with the size of the monomeric α-7 nAChR ECD. It should be noted that these results were in agreement with the expression of human neuronal nicotinic receptor α4 and β2 subunits in P. pastoris, which were also expressed in glycosylated forms [20]. Besides P. pastoris, the glycosylation of recombinant α-7 nAChR was also detected in the proteins expressed in Xenopus oocytes [21].…”
Section: Purification Of Recombinant Human α-7 Nachr Ecdsupporting
confidence: 84%
“…At present, most studies about the relationship between nicotine administration and cannabinoid system are related to the addiction of nicotine [ 33 35 ]. Although nAchRs, including α 3-, α 4-, and α 7-AchRs, are believed to be involved in nicotine-induced bioactivities [ 36 38 ], and a study reported that α 3-nAchR and CB2 receptor were expressed in the same neural cells of brain tissue in mice [ 39 ], additional studies are needed to explore the mechanism that nicotine stimulates CB2 receptor and increases its expression.…”
Section: Discussionmentioning
confidence: 99%
“…We found a strategy to clone large fragments of DNA by dividing them to short PCR fragment cloning, followed by restriction digestion and ligation cloning 9 . This strategy shows dominance in amplifying efficiency, it helps overcome PCR problem, and constructs very big clones without turning to complex reagents and technologies, like Red/ET system 10 or TAR system 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%